Parental kidnapping in America an historical and cultural analysis - Dabbagh, Maureen, 1958-; ebrary, Inc. (Jefferson, N.C. : McFarland & Co., 2012)
"In 2010, the U.S. Department of Justice reported an average of 200,000 cases of parental kidnapping each year. This candid exploration from the eighteenth century to the present clarifies many misconceptions and reveals how the external influences of American social, political, legal, and religious culture can exacerbate family conflict, creating a social atmosphere ripe for abduction"--Provided by publisher.
Parental abduction: a timeless tradition -- The progressive era and the family -- Culture, blood and borders -- The military, war, and parental kidnapping -- Religion: motivation for abduction -- Heroes and outlaws -- Nationalism and the Hague -- Domestic violence, child abuse, and alienation -- Law enforcement and parental kidnapping -- Reunification -- Prevention -- Politics of abduction -- Evolution of an epidemic.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Parental kidnapping -- United States -- History; Electronic books